An active noise cancellation technique for the CUORE Pulse Tube cryocoolers. (July 2018) - D'Addabbo, A.; Bucci, C.; Canonica, L.; Di Domizio, S.; Gorla, P.; Marini, L.; Nucciotti, A.; Nutini, I.; Rusconi, C.; Welliver, B.
Highlights: A technique for active cancellation of Pulse Tube (PT) vibrational noise is proposed. The technique controls the relative phase of the pressure waves of two or more PTs. A scan of the phase parameter space allows to find the lowest noise configuration. The PTs are driven locking their relative phases in the optimal working condition. Abstract: The Cryogenic Underground Observatory for Rare Events (CUORE) experiment at Gran Sasso National Laboratory of INFN searches for neutrinoless double beta decay using TeO2 crystals as cryogenic bolometers. The sensitivity of the measurement heavily depends on the energy resolution of the detector, therefore the success of the experiment stands on the capability to provide an extremely low noise environment. One of the most relevant sources of noise are the mechanical vibrations induced by the five Pulse Tube cryocoolers used on the cryogenic system which houses the detectors. To address this problem, we developed a system to control the relative phases of the pulse tube pressure oscillations, in order to achieve coherent superposition of the mechanical vibrations transmitted to the detectors. In the following, we describe this method and report on the results in applying it to the CUORE system.